Optimizing Performance Excellence: Revealing the Relationship Between SOP Implementation and ASN Performance - Sabtian, Yoki Tulus; Natasha, Catherine Eugene (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
In today's quest for efficiency and accountability, governments worldwide focus on optimizing their State Civil Service's (ASN) performance, vital for delivering satisfactory public services. Many adopt Standard Operating Procedures (SOPs) to regulate and enhance ASN performance. This research employs qualitative methods, including questionnaires filled out by government employees, to explore how SOP implementation affects ASN. Effective use of SOPs improves clarity and efficiency but must strike a balance to avoid overregulation. SOPs play a crucial role in fostering ASN performance through understanding and recognition, requiring consistency, training, leadership, rewards, and evaluation for success. Overall, implementing SOPs significantly impacts ASN's performance, enhancing public services and governance.